LAT1 activity of carboxylic acid bioisosteres: Evaluation of hydroxamic acids as substrates. Issue 20 (15th October 2016) - Zur, Arik A.; Chien, Huan-Chieh; Augustyn, Evan; Flint, Andrew; Heeren, Nathan; Finke, Karissa; Hernandez, Christopher; Hansen, Logan; Miller, Sydney; Lin, Lawrence; Giacomini, Kathleen M.; Colas, Claire; et al.
Graphical abstract: Abstract: Large neutral amino acid transporter 1 (LAT1) is a solute carrier protein located primarily in the blood–brain barrier (BBB) that offers the potential to deliver drugs to the brain. It is also up-regulated in cancer cells, as part of a tumor's increased metabolic demands. Previously, amino acid prodrugs have been shown to be transported by LAT1. Carboxylic acid bioisosteres may afford prodrugs with an altered physicochemical and pharmacokinetic profile than those derived from natural amino acids, allowing for higher brain or tumor levels of drug and/or lower toxicity. The effect of replacing phenylalanine's carboxylic acid with a tetrazole, acylsulfonamide and hydroxamic acid (HA) bioisostere was examined. Compounds were tested for their ability to be LAT1 substrates using both cis -inhibition and trans -stimulation cell assays. As HA-Phe demonstrated weak substrate activity, its structure–activity relationship (SAR) was further explored by synthesis and testing of HA derivatives of other LAT1 amino acid substrates (i.e., Tyr, Leu, Ile, and Met). The potential for a false positive in the trans -stimulation assay caused by parent amino acid was evaluated by conducting compound stability experiments for both HA-Leu and the corresponding methyl ester derivative. We concluded that HA's are transported by LAT1. In addition, our results lend support to a recent account that amino acid esters are LAT1 substrates, and that hydrogen bonding may be as important as charge for interaction with the transporter binding site.